Cultivation of Agaricus blazei in the environmental protection area of the Baturité region under three types of casing soils - Cavalcante, José Luis Rocha (2008)
The outdoor cultivation (ditches) of Agaricus blazei was evaluated in the protected natural area (APA) of the mountainous region of Baturité on three types of casing soils (A, B and C). Casing soil A (horizon A) of the local soil was used (Alfisol). Casing B was obtained with a mixture of 30% of eucalyptus charcoal (1-2 cm of length) and 70% of horizon B of the local soil. Casing C was composed of 25% of vermiculite, 25% of coconut fiber and 50% of coarse sand. Temperature, relative humidity and pluviometric rates were monitored. The physical-chemical properties of the three casing soils were analyzed. The effect of the casing soil on the number and weight of the mushrooms, productivity, yield and biological efficiency of A. blazei were evaluated. The yield, productivity, biological efficiency and number of mushrooms were higher when using soil A. The highest productivity for soil A was attributed mainly to the physical characteristics, which were considered more appropriate for the cultivation, in addition to the high pluviometric rates and relative humidity. The productivity with soil A (9.62%) is comparable with the average productivity obtained in Brazil, meaning that the cultivation of A. blazei in this APA may have good perspectives for cultivation.